Collective Self-Determination: How the Agent of Help Promotes Pride, Well-Being, and Support for Intergroup Helping. (May 2017) - Thomas, Emma F.; Amiot, Catherine E.; Louis, Winnifred R.; Goddard, Alice
This research integrates self-determination theory and the social identity approach to investigate the notion of collective (group level) self-determination, and to test how the agent of intergroup help (helping initiated by a group representative versus group members) shapes group members' motives and support for intergroup helping. Study 1 ( N = 432) demonstrates that collective self-determination predicts support for intergroup helping, group pride, and well-being, over and above individual-level self-determined motivation. Study 2 ( N = 216) confirmed that helping by group members was seen as more collectively self-determined than helping by a group representative, producing effects on pride, well-being, and support. Study 3 ( N = 124) explores a qualifier of these effects: People who identify more strongly with the leader who is providing the help also experience representative helping as more collectively self-determined, thereby promoting well-being, group pride, and support. Findings highlight the value of integrating self-determination theory with intergroup theories to consider collective aspects of self-determination.